Az Osztrák-Magyar Monarchia geostratégiai és katonaföldrajzi kényszerei - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2009)
In a geopolitical aspect the Austro–Hungary was a complex geostrategical and military geographical formation which had a long political and geographical developing process. In this process coherent and spread geographical factors appeared which entered into balance for centuries and the effects of those factors reserved the Habsburg Empire and Austro–Hungary. This empire had become a Danubian empire which had some geostrategical factors: for example geographical glacises, balanced territorial features, almost closed military geographical borders, centralization effects of geographical basins and central position. The author presents those factors, a geographical developing process of the Austro–Hungary and summarizes the geostrategical position of the Monarchy in the First World War. This essay presents that the joint application of these different factors can help to understand the process of the Austro-Hungarian Empire’s existence and its disintegration.